Afectación de las propiedades físicas y mecánicas del hormigón bajo influencia microbiana acelerada - Jeferson Javier, Acán Paca (2019)
The objective of this work was to determine the variation of the physical and mechanical properties of concrete against the action of Thiobacillus Thiooxidants. To achieve our goal, samples were taken from the concrete walls of the tanks of the wastewater treatment plant in the La Libertad sector. These samples were subjected to constant stirring and temperature conditions, which allowed Thiobacillus Thiooxidants to be isolated, whose growth control parameters were carried out with the optical density method, where the absorbance was measured, the concentration of and , in addition to counting in the Neubauer chamber to determine the number of CFUs. The inoculation process was carried out for 45 days, with 18 cubic mortar specimens where compressive strength, weight and pH variation were monitored every 15 days, 9 specimens were immersed in a solution of sulfuric acid with a pH of 5 and 9 specimens were submerged in the inoculum. During the control process it was found that the samples submerged in the acid solution did not show significant variations in the compression, weight and pH controls. However, the samples submerged in the inoculum presented a loss of resistance of 39%, in addition to a notable increase in the acidity of the mortar, these results lead us to conclude that the action of Thiobacillus Thiooxidants causes considerable alterations in physical and mechanical properties of concrete, which are reflected in the loss of resistance and weight loss.